The European civil society campaign on the financial transaction tax - Peter Wahl (International Labour Organization (ILO), 2014)
The Financial Transaction Tax (FTT) has been a spearhead demand of civil society for some 15 years now. Initially put on the table by the UNDP in 1996 as an instrument of innovative financing for development, also its regulatory dimension surfaced after the Asian financial crisis 1997/98. While some governments were open to the idea, in particular France and Belgium, there was strong opposition from other countries such as the US and the UK and of the finance industry. Therefore, the FTT seemed to be doomed to disappear from the agenda. The financial crash in 2008, however, was a game changer and the FTT had its come back with France and Germany as driving force behind it. After a failed attempt to get an agreement in the G20, the EU presented a draft directive, which was very close to the expectations of civil society. But as strong objections among the EU-27 occurred, in particular from the UK, a coalition of eleven countries chose the option of Enhanced Cooperation to implement the tax. The Enhanced Cooperation Procedure is part of the EU regulations and can be used for projects, which cannot be agreed among all 27 member states but have the support of at least nine member states. In February 2013 the Enhanced Cooperation Procedure was launched officially on the basis of a revised draft by the EU-Commission, which was even stricter vis à vis the financial sector, in particular through its strong and innovative provisions against tax evasion. The resistance of the finance industry against the FTT continued. Their lobby organised a campaign in order to reach at least a watering down of the proposal. Hence, the definitive outcome of the ongoing process is still open. For civil society the process is nevertheless a great success by now. The European
Keywords: 330; financial management; taxation; economic recession; Community law; regulation; comment; public opinion; trade union role; EU countries